Transcatheter management of aorto-right ventricular tunnel: A surprise in the catheterization laboratory - Muthusamy Kalyanasundaram; Abhishek Kasha; Sai Gopalakrishnan; Kaushik Jothinath (Wolters Kluwer Medknow Publications, 2022)
Herein, we report successful device closure of aorto-right ventricular tunnel (ARVT) in a 2 year-old-boy presenting with recurrent respiratory tract infection and poor weight gain. He was initially diagnosed with coronary arteriovenous fistula after the clinical examination and echocardiogram. However, his cardiac catheterization revealed ARVT. Although most of the aorto-ventricular tunnels are managed by surgical intervention, we successfully managed our case with transcatheter intervention.